Stay Home : Housing and Home in the UK during the COVID-19 Pandemic - Tunstall, Rebecca (Book collections on Project MUSE., 2022)
The COVID-19 pandemic has dramatically exposed weaknesses in UK housing's relationship to the labour market and welfare system. Inequalities in household type, home occupancy, housing cost and security have contributed to the unequal impact of the disease. Comprehensively charting fast-moving and inter-linked policy developments, Becky Tunstall assesses the position of housing and home in public policy, health and in peoples' lives, and documents the most immediate responses to the pandemic, for students, scholars and practitioners.